2011
DOI: 10.1007/s12010-011-9389-6
|View full text |Cite
|
Sign up to set email alerts
|

Multienzymatic Sucrose Conversion into Fructose and Gluconic Acid through Fed-Batch and Membrane-Continuous Processes

Abstract: Multienzymatic conversion of sucrose into fructose and gluconic acid was studied through fed-batch and continuous (in a membrane reactor) processes. The law of substrate addition (sucrose or glucose) for the fed-batch process which led to a yield superior to 80% was the decreasing linear type, whose feeding rate (ϕ; L/h) was calculated through the equation: ϕ = ϕ(o) - k.t, where ϕ(o) (initial feeding rate, L/h), k (linear addition constant, L/h (2)), and t (reaction time, h). In the continuous process, the yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The use of particular enzymes reduces the concentration of selected sugars in juices. Glucose can be converted into gluconic acid due to the use of two different enzymes: glucose oxidase and catalase [ 65 ]. Fructose can be converted into D-allulose (one of the rare sugars and a low-caloric sugar) by using D-allulose 3-epimerase [ 66 ] or into sorbitol by using a glucose-fructose oxidoreductase [ 67 , 68 ].…”
Section: Techniques Used In Reducing the Sugar Content Of Juicesmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of particular enzymes reduces the concentration of selected sugars in juices. Glucose can be converted into gluconic acid due to the use of two different enzymes: glucose oxidase and catalase [ 65 ]. Fructose can be converted into D-allulose (one of the rare sugars and a low-caloric sugar) by using D-allulose 3-epimerase [ 66 ] or into sorbitol by using a glucose-fructose oxidoreductase [ 67 , 68 ].…”
Section: Techniques Used In Reducing the Sugar Content Of Juicesmentioning
confidence: 99%
“…Applying specific enzymes can improve the efficiency and quality of food products with low costs by improving nutritional safety, reducing energy costs related to the process, and leading to process optimization [ 71 ]. Biotechnology processes catalyzed by enzymes are carried out under smooth pH and relatively low temperature, which is especially important in the case of sensitive substances, and they exhibit high stereochemical selectivity [ 65 ]. On the other hand, some of the enzymatic processes require preliminary steps: liquefaction, gelatinization, saccharification, and purification or hydrolysis of polysaccharides.…”
Section: Techniques Used In Reducing the Sugar Content Of Juicesmentioning
confidence: 99%
See 2 more Smart Citations
“…This enzyme-powered device was successfully employed in Catalysis Science & Technology Mini review the autonomous and on-demand delivery of doxorubicin in HeLa cancer treatment. 307 Some studies reported the use of maltose and sucrose as substrates for D-gluconic acid production in batches using catalase to destroy the hydrogen peroxide 21,308,309 and using fed-batch, 310 continuous 311 and membrane-continuous 309,310 processes. In general, all processes were satisfactory, reaching high yields of conversion of maltose and sucrose to D-gluconic acid.…”
Section: Conversion Of Disaccharides To D-gluconic Acidmentioning
confidence: 99%